(untitled) (Indian Journal of Applied-Basic Medical Sciences, 2022)
Background:Lower limbs are commonly involved in cellulitis as they are more susceptible to injuries. This study analyses various causes and risk factors for cellulitis in non-diabetics. Method: This retrospective observational study was conducted at department of surgery,AMCMET medical college and Sheth L.G. Hospital, Mani Nagar, Ahmedabad and included 30 nondiabetic patients. The severity of cellulitis was graded according to CREST guidelines.Demographics, Risk factors, grades, management and treatment outcomes were recorded and analyzed.Results: Cellulitis was more common in males and in young adults. It was more unilaterally and resulted more commonly by trauma. Severe grades needed surgical intervention. Conclusions: Non diabetic patients with lower limb cellulitis can also result in severe morbid consequences but in the absence of co-morbid illness, they usually recover with minimal residual disabilities.